Histórias e memórias do curso comercial do Colégio São Carlos de Caxias do Sul/RS (1940-1969) - Pedri, Elen Lemaire (My University, 2022)
This study has researched the history of the Business Course at the Technical Business School of São Carlos High School, in Caxias do Sul - RS state - Brazil. The source material is based on the memoir given by graduate students from the period between 1940 and 1969. São Carlos School began its activities in 1936 with primary school and dedicated its efforts to women's education. Due to the economic growth of the city during the period that was studied, the school sought to adapt to the new times and, in 1940, it started to offer the Technical Business Course, attached to Carmo School, training accountant ladies. Through Brazilian and regional context, this work's objective was to analyze stories and memories of the constitution process of the Business Course at São Carlos High School in Caxias do Sul/RS, between 1940 and 1969, showing how they intertwined with the formative trajectories of the interviewed graduates. It was also analyzed how the training experience contributed to the constitution of the graduates' identities associated with the professional practice in the technical course. Studies on the subject were developed through Oral History and the analysis of documents available at the school, the João Spadari Adami Municipal Historical Archive and newspaper clippings from that time. In addition, the theoretical assumptions developed here refer to Cultural History, History of Education, school culture, professional identity, among others. The Business Course, which began in 1940, offered the female contingent another possibility of training, in addition to those available at the time, such as teaching. Regarding the interviews carried out and the intertwining between the course and accounting practice, it is noted that the study of accounting theory was not sufficient for the execution of the profession itself, but the access to work, parallel to studies in college, contributed significantly for the maintenance of the interviewees' professional identities. Therefore, this research tells the history of the Business Course, specifically of São Carlos School, as a historical production, but also providing opportunities to contribute to other researches related to accounting education, especially with female participation in the optimization processes of the accounting area. [resumo fornecido pelo autor]
O presente estudo investigou a história do Curso Comercial da Escola Técnica do Comércio do Colégio São Carlos, em Caxias do Sul/RS, a partir das memórias de egressas do período compreendido entre 1940 e 1969. O Colégio São Carlos iniciou suas atividades em 1936 com o curso primário e dedicou seus esforços à educação feminina. Devido ao crescimento econômico da cidade no período estudado, a escola buscou adaptar-se aos novos tempos e, em 1940, passou a oferecer o Curso Técnico do Comércio, anexo ao Colégio do Carmo, formando peritas-contadoras. Mediante a contextualização brasileira e regional, objetivou-se analisar histórias e memórias do processo de constituição do Curso Comercial do Colégio São Carlos de Caxias do Sul/RS, entre 1940 e 1969, evidenciando o modo como se entremearam às trajetórias formativas de egressas. Também, analisou-se como a experiência formativa contribuiu para a constituição de identidades das egressas associadas à prática profissional do curso técnico. Os estudos sobre o tema foram desenvolvidos por meio da História Oral e da análise de documentos disponíveis junto à escola, ao Arquivo Histórico Municipal João Spadari Adami e aos recortes de jornais da época. Além disso, os pressupostos teóricos desenvolvidos referem-se à História Cultural, História da Educação, cultura escolar, identidade profissional, dentre outros. O Curso Comercial, iniciado em 1940, trouxe ao contingente feminino outra possibilidade de formação, além das disponíveis à época, como no caso do magistério. Em relação às entrevistas realizadas e ao entrelaçamento entre o curso e a prática contábil, nota-se que o estudo da teoria contábil não foi suficiente para a execução da profissão propriamente dita, mas o acesso ao trabalho, paralelo aos estudos no colégio, contribuiu significativamente para a manutenção da identidade profissional. Sendo assim, esta pesquisa conta a história do Curso Comercial, especificamente do Colégio São Carlos, constituindo-se de uma produção histórica, mas também oportunizando contribuir com outras pesquisas relativas à formação contábil, especialmente à participação feminina nos processos de otimização da área contábil. [resumo fornecido pelo autor]
Keywords: Colégio São Carlos - Caxias do Sul (RS) - História; Ensino técnico - Caxias do Sul (RS) - História; Contabilidade; Colégio São Carlos - Caxias do Sul (Brazil) - History; Technical education - Caxias do Sul (Brazil) - History; Accounting